Chemical constituents of the root bark of Erythrina droogmansiana. (June 2017) - Bedane, Kibrom Gebreheiwot; Kusari, Souvik; Bullach, Anke; Masesane, Ishmael B.; Mihigo, Shetonde O.; Spiteller, Michael; Majinda, Runner R.T.
Graphical abstract: Highlights: Two new flavanoids along with eight known compounds were isolated from the root bark of Erythrina droogmansiana . The structures were elucidated based on spectroscopic analyses (1D- and 2D-NMR and ESI-HRMS). Some of the isolated compounds showed remarkable DPPH radical scavenging activities. Abstract: Two new compounds namely 7, 4′-dihydroxy-2′-methoxy-3′-(3-methylbut-2-enyl)isoflavanone (1 ) and 5, 7, 3′-trihydroxy-8-(3-methylbut-2-enyl)-[6′′, 6′′-dimethylpyrano(2′′, 3′′:4′, 5′)]isoflavone (4 ) were isolated from the root bark of Erythrina droogmansiana together with eight known compounds. Their structures were elucidated on the basis of spectroscopic analyses (1D- and 2D-NMR and ESI-HRMS) and by comparison with literature data. In addition, the correct 13 C NMR of 5, 7, 2′, 4′-tertahydroxy-8, 5′-di-(3-metylbut-2-enyl)isoflavone(6) was assigned. The DPPH free radical scavenging properties of the isolated compounds were evaluated. Compounds4–7 showed weak to moderate DPPH free radical scavenging activities.